Observation of the Production of Three Massive Gauge Bosons at √s=13 TeV; Physical Review Letters; Vol. 125, iss. 15 - Sirunyan A. M.; Tumasyan A. R.; Adam W. Wolfgang; Ambrogi F. Federico; Tyurin N. E. Nikolay Evgenjevich; Babaev A. A. Anton Anatoljevich; Sukhikh L. G. Leonid Grigorievich (2020, 2020)
Title screen